Systematic Literature Review: Facilitation Strategies in Developing Organizational Capability and Enhancing Employee Learning - Rianzah Munawaroh; Eni Noviani; F. Danardana Murwani; Ludi Wishnu Wardana (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This research is a Systematic Literature Review (SLR) that aims to identify, analyze, and synthesize scientific literature related to effective facilitation strategies in the context of organizational capability development and employee learning improvement. The main focus of this research is to map various forms of facilitation interventions, assess their impact on organizational capabilities such as innovation, adaptability, and efficiency, and explore the role of facilitation in strengthening organizational and individual learning mechanisms. By using an SLR approach that follows the guidelines of PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses), this study ensures transparency and replication of the study process. The results of the synthesis show that facilitation strategies contribute significantly to improving organizational capabilities through the creation of a collaborative learning environment, strengthening communication, and improving employees' adaptive skills. In addition, facilitation has been proven to support the integration of new knowledge into organizational practices, thereby strengthening competitiveness and sustainability. These findings are expected to provide evidence-based guidance for practitioners in designing effective facilitation interventions, as well as a theoretical basis for future researchers to develop studies on the relationship between facilitation, learning, and organizational capabilities.